Pembuatan dan Karakterisasi Scaffold Hidroksiapatit (HAp) dari Limbah Tulang Ikan Tenggiri (Scomberomorus commerson) - Rohania, Meisa; Deswardani, Frastica; Fendriani, Yoza; Anjelina, Ria; Anggraini, Rista Mutia; Maulana, Lucky Zaehir; Pujaningsih, Febri Berthalita (Jurusan Fisika, Universitas Bangka Belitung, 2025)
Defects in bone tissue represent a significant health concern and continue to pose challenges in clinical surgery. The fabrication of scaffolds from hydroxyapatite (HAp) can support bone regeneration. However, producing HAp scaffolds with ideal pore structures for effective bone tissue engineering remains difficult. In recent decades, many studies have attempted to enhance HAp scaffolds by incorporating polymeric materials to address their limitations. In this study, corn starch was used as a pore-forming agent, and polyvinyl alcohol (PVA) served as a binder and pore size regulator. The scaffolds were fabricated using the freeze-drying method, which offers the advantage of forming porous structures while maintaining scaffold integrity. This study investigated the effects of varying PVA additions which 3 wt%, 7 wt%, and 10 wt%. XRD analysis showed that the diffraction peaks of all samples corresponded to the HAp phase, displayed β-TCP peaks, and a crystal size with values ranging from 0.96 nm to 11.77 nm. SEM analysis showed that the HAp-7 scaffold has the largest pore size distribution range of about 1.19 µm to 11.77 µm.